The application of pulsed laser deposition for the fabrication of thin films of materials for medicine - Muryna, Maryia (Univerzita Pardubice, 2023)
This bachelor's thesis focuses on the application of pulsed laser deposition for the fabrication of thin films that are used to enhance the quality of medical materials. It provides a detailed description of the PLD process, its mechanism, and equipment for a better understanding of how this technique functions. Additionally, it showcases specific studies where PLD has been successfully applied to deposit various materials, serving as examples of its effectiveness in the field of medical materials.
Využití pulzní laserové depozice pro přípravu tenkých vrstev medicinálních materiálů
Keywords: pulzní laserová depozice; tenké vrstvy; medicinální materiály; biokompatibilita; implantáty; pulsed laser deposition; thin films; medical materials; biocompatibility; implants